2020
DOI: 10.3390/cells9102161
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lamin B1 Levels Promote Cell Migration by Altering Perinuclear Actin Organization

Abstract: Cell migration requires reposition and reshaping of the cell nucleus. The nuclear lamina is highly important for migration of both primary and cancer cells. B-type lamins are important for proper migration of epicardial cells and neurons and increased lamin B to lamin A ratio accelerates cancer cell migration through confined spaces. Moreover, a positive association between lamin B1 levels and tumor formation and progression is found in various cancer types. Still, the molecular mechanism by which B-type lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Interestingly, LMNB1-associated disorders seem to share the fact that the Lamin B1 level of expression (either increased or decreased in different disease models) is responsible for the pathological phenotype, suggesting a very close relation between a morphological, physical, and functional balance [35]. Several new evidences also suggest that Lamin B1 levels can be relevant for cell migration mechanisms, neurogenesis control, and cellular aging [37][38][39]. Stemming from these reflections, our astrocytic in vitro ADLD cellular model highlighted new molecular and functional insights that could give new clues to this biological and pathological intriguing puzzle.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, LMNB1-associated disorders seem to share the fact that the Lamin B1 level of expression (either increased or decreased in different disease models) is responsible for the pathological phenotype, suggesting a very close relation between a morphological, physical, and functional balance [35]. Several new evidences also suggest that Lamin B1 levels can be relevant for cell migration mechanisms, neurogenesis control, and cellular aging [37][38][39]. Stemming from these reflections, our astrocytic in vitro ADLD cellular model highlighted new molecular and functional insights that could give new clues to this biological and pathological intriguing puzzle.…”
Section: Discussionmentioning
confidence: 99%
“…A thorough search of the relevant literature did not yield any publicationsthat report a peri-nuclear force or the actin cap in cancer cells. An indirect study on melanoma cancer cells demonstrated that the actin rim (another peri-nuclear actin organization located around but not covering the nucleus) reduces cell migration rates 41 , indirectly suggesting the existence of a peri-nuclear force.…”
Section: Discussionmentioning
confidence: 99%
“…We do not find any publications available that report peri-nuclear force or actin-cap in cancer cells. An indirect study on melanoma cancer cells demonstrated that the actin rim (another peri-nuclear actin organization that is located around but not covering the nucleus) reduces cell migration rates [30], indirectly suggesting the existence of peri-nuclear force. However, no direct experimental data are reported.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, overexpression of Lamin A facilitates the formation of actin-rim and restricts the cancer cell migration. Overexpression of Lamin B reduces the actin-rim formation and promotes migration[30]. Peri-nuclear force might be involved in this process due to the existence of peri-nuclear actin organization and the effect of Lamin A.…”
Section: Discussionmentioning
confidence: 99%